Thermo‐controlled, self‐released smart wood tailored by nanotechnology for fast clean‐up of highly viscous liquids. Issue 1 (4th July 2022) - Cai, Yahui; Wu, Jianfei; Wang, Kaili; Dong, Youming; Hu, Jundie; Qu, Jiafu; Tian, Dan; Li, Jianzhang; Fu, Qiliang
Abstract: Designing highly porous materials is of great importance for liquid separation, water purification, and disinfection, such as spill oil cleaning and recycling, seawater desalting, and oil/water separation. However, a remaining challenge is to produce porous materials with the characteristics of fast absorption, continuous directional transport, and self‐release of viscous liquid. Herein, a functional cellulosic composite is reported by the chemical treatment and functionalization of wood resulting in a smart wood that can thermally self‐release and separate high viscosity oil. The smart wood has a high absorption speed of 1398 mL/(m 2 ·s) (ethylene glycol) and a maximum absorption capacity of 47.2 g/g (chloroform) due to its intrinsic vertical micro/nanoscale channel structure, low tortuosity, and high porosity. Moreover, the switchable wettability is achieved by the surface coating of poly(N‐isopropylacrylamide) on the porous wood, which enables the collection and removal of oil from the oil/water mixture. The high viscosity oil can be automatically released due to the passive oil release at room temperature. The release capacity of the smart wood remains above 91% after 15 cyclic tests. We envision that this functional smart wood could be extended to a wide range of applications in smart hydrogels, microfluidics, artificial drug release, and environmental restoration. Abstract : Wood nanotechnologies are developed to manipulate and functionalized the nanostructure of bulk wood resulting in a smart wood with a switchable wettability, high porosity, and low tortuosity. This smart wood has a high absorption speed and capacity, as well as self‐released characteristics, which are comparable to most random pore absorbents and could be potentially applied to clean up oil spills or oil/water mixtures.